Growth Issues in Developing Countries : Natural Resources, Institutions and Economic Growth - Ihnátová, Ivana; Křečková Kroupová, Zuzana, 1972-; Erreygers, Guido; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
The dissertation examines the relationship between natural resource abundance and economic growth with respect to the role of institutions. We find that the theory of the natural resource curse is especially relevant to developing countries. However, they may balance out the curse and even benefit from their resource wealth by improving their institutional quality. The analysis employs various proxies for the quality of institutions. According to the results, the Economic Freedom of the World seems to be the most suitable one, which emphasises the importance of economic aspects. In addition, the findings support the assumption that the resource curse was more likely to occur in the past than nowadays as the value of the economic freedom index used to be lower in most countries.
Vedoucí práce: Zuzana Křečková Kroupová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: economics of globalisation and european integration [obor dipl. práce]; diplomové práce; master's theses